Exploring and Dealing with Issues of ‘Identity And Difference’ at My Workplace Context in Surabaya - Asmani, Almodad B. (Bina Nusantara University, 2008)
Article explored the ways an identity was shaped within societies and how these might have affected the work as an EFL teacher in a workplace context. Data were collected from reflective data that was autobiography and other related research. Analysis was done by analyzing autobiography that was working environment approach and reflection analysis. It can be concluded that awareness of global context, local knowledge, and ability to listen support English teaching activities having many differences and the available condition.Â